Measurement of rotational temperature at Kolhapur, India - Mukherjee, G.K.; Parihar, Navin (My University, 2004)
Measurements of the hydroxyl rotational temperature for the (8,3) Meinel band have been reported from the observations of the ratio of the relative intensities of P1(2) and P1(4) lines of the OH(8,3) band at Kolhapur (16.8° N, 74.2° E, dip lat. 10.6° N) in India during the period 1 November 2002-29 April 2003 using tilting-filter photometers. Mean values of rotational temperature have been computed for 60 nights. The monthly mean value of temperature lies in the range 194(±11)-208(±18)K. The mean rotational temperature obtained from all the measurements was found to be 202±15K. The results agree with other low-latitude measurements of rotational temperature using photometric airglow techniques. Quasi-periodic fluctuations with a period of about one to two hours have been prominent on many nights. Furthermore, the results show the general agreement between observations and model (MSIS-86) predictions.
Keywords: Atmospheric composition; Atmosphere density; Atmospheric structure; Kolhapur